Seroprevalence of Mycoplasma bovis in grazing dairy cows from five different areas in Serbia - Vojinovic, Dragica; Zdravkovic, Nemanja; Prodanović, Radiša; Vujanac, Ivan; Nedić, Svetlana; Giadinis, Nektarios D.; Panuonis, Nikolaos; Manic, Marija Manic; Bugaraski, Dejan; Palamarevic, Milija; Bogicevic, Nataša; Dobrosavljevic, Ivan; et al. (Journal of the Hellenic Veterinary Medical Society, 2019)
Mycoplasma bovis infection in grazing dairy cows has not been reported in the Republic of Serbia to date. It is important to monitor its seroprevalence on the field. The presence of specific antibodies against M. bovis in the blood serum of grazing dairy cows is investigated in the present study. A total of 131 blood serum samples of clinically healthy dairy cows were examined. Sampling was performed during 2013 from five different areas in Serbia: Zasavica, Pozarevac, Gruza, Novi Sad and Banatski Karlovac. A commercial ELISA kit for diagnosis of M. bovis antibodies in blood serum samples, manufactured by Bio-X Diagnostics, Belgium, was used. Specific antibodies against M. bovis were identified in 13 out of 131 samples (9.92%) from 4 locations; the only negative location was the most southern Gruza. The revealed seroprevalence is evidence for the presence of M. bovis in grazing dairy cows in different locations of Serbia.